Protective Immunity Induced by TgMIC5 and TgMIC16 DNA Vaccines Against Toxoplasmosis - Zhu, Yu-Chao; Ma, Li-Juan; Zhang, Ji-Li; Liu, Jian-Fa; He, Yong; Feng, Ji-Ye; Chen, Jia (Frontiers in Cellular and Infection Microbiology, 2021)
Toxoplasma gondii is an obligate intracellular parasite, leading to a globally distributed zoonosis. Effective and secure vaccine against toxoplasmosis are necessary to be developed. The aim of this study is to evaluate the immune efficacy of DNA vaccines encoding TgMIC5 and TgMIC16 genes against T. gondii infection. The recombinant plasmid pVAX-MIC5 and pVAX-MIC16 were constructed and injected into mice intramuscularly. The specific immune responses and protective efficacy against T. gondii infection were evaluated by cytokine detection and serum antibody measurements, lymphocyte proliferation assays, flow cytometry of lymphocytes and the evaluation of survival time and cysts reduction after challenge with the T. gondii RH tachyzoites and PRU cysts, respectively. The results indicated that immunized mice showed significant increase of IgG, IFN-γ, IL-2, IL-12p70, IL-12p40 and percentages of CD4+ and CD8+ T cells, as well as prolonged survival time and reduced brain cysts compared with controls, with the best detection index rather than the groups immunized with two-gene cocktail of pVAX-MIC5 + pVAX-MIC16, which is rather than the groups immunized with single gene of pVAX-MIC5 or pVAX-MIC16. These results demonstrated that TgMIC5 and TgMIC16 could induce effective immunity against toxoplasmosis and provide potential vaccine candidates to develop anti-T. gondii vaccine.